1999
DOI: 10.1093/humrep/14.4.976
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre efficacy and safety study of the single contraceptive implant Implanon

Abstract: An open, multicentre study was performed to assess efficacy, safety and acceptability of the single-rod contraceptive implant Implanon. The study involved 635 young healthy women, who were sexually active and of childbearing potential. The women were followed up every 3 months over the entire study period. Originally the study was designed for 2 years, but was extended to 3 years in a group of 147 women from two centres. Altogether, 21 centres in nine different countries participated. The average age of the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
2
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(111 citation statements)
references
References 11 publications
4
99
2
6
Order By: Relevance
“…Our observed continuation rate of 83.0% overall is similar to the other published 12-month continuation rates of the etonogestrel implant. (13,14) Few studies have specifically evaluated continuation of the implant after immediate postabortion insertion. Women undergoing immediate postabortion placement may have had less time to consider their contraceptive decision and may be more likely to regret their choice, leading to higher discontinuation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Our observed continuation rate of 83.0% overall is similar to the other published 12-month continuation rates of the etonogestrel implant. (13,14) Few studies have specifically evaluated continuation of the implant after immediate postabortion insertion. Women undergoing immediate postabortion placement may have had less time to consider their contraceptive decision and may be more likely to regret their choice, leading to higher discontinuation rates.…”
Section: Discussionmentioning
confidence: 99%
“…of cases having amenorrhea infrequent bleeding. Similarly Haracio and Craxatto et al (1999) (10) showed that maximum no. (17.2%) of cases were having bleeding irregularities same cases were having amenorrhea in reference period.…”
Section: Frequent Bleedingmentioning
confidence: 83%
“…11(10%) of cases discontinued implant due to no fix pattern of bleeding 7(6.63%) due to prolonged bleeding, 7(6.63%) due to heavy bleeding, One case (0.90%) discontinued for next conception. Croxatto et al (1999) reported maximum reasons (17.2%) were discontinuation bleeding irregularities. Buckshee et al (1993) (11) noted in their study maximum no.…”
Section: Frequent Bleedingmentioning
confidence: 98%
“…An initial history and examination is performed to verify that an Implanon™ was inserted and to locate the insertion site. There have been a number of documented cases in which Implanon™ devices were not in fact inserted, but left within the introducer [6,7]. It is therefore important to try and verify that an Implanon™ device has been placed.…”
Section: Discussionmentioning
confidence: 99%